Preorganizational diagnostic of fish community - Loría Paniagua, Dennis (2018)
The Costa Rican Institute of Fishing and Aquaculture (INCOPESCA), through the Ministry of Agriculture and Livestock (MAG), asked the School of Economics and Agribusiness at the University of Costa Rica (EEAA), a technical approach in analyzing a diagnosis pre organizational for the fishing community. This institutional initiative comes as a concern by the INCOPESCA in order to improve the socioeconomic situation of the inhabitants of that community.  The community studied has a population of 62 inhabitants between 0 and 74 years of age, of whom 49% are men and the remaining 51% women. The primary activity is subsistence fishing and shellfish extraction, whose products are marketed in the Central Market of Puntarenas.  This fishing property is characterized by a marked division that constantly undermines community work together in integrated projects that benefit the people. Given these situations, methodologically pre organizational analysis focused on the socio-organizational, economic, productive and environmental dimensions. The development of this process was guided by a team of EEAA and seniors Greece Campus of the University of Costa Rica.  It was concluded that there is institutional capacity to support the fishing community, however you need to work on a comprehensive training program in areas of human, organizational and business development in the short term, people in the community to adopt an organizational figure enabling them to improve their socio-economic and productive conditions.